Element Size Effects in Nonlinear Analysis of Reinforced Concrete Beams without Web Reinforcement - Tavio Tavio (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
A new approach is developed to the nonlinear analysis of reinforced concrete beams without stirrups subjected to a monotonically increasing loading from zero up to the ultimate load. The softening effect of concrete in tensioncompression, the tension-stiffening and tension-softening of concrete in tension are all taken into account in the proposed model. The effect of finite element mesh size is investigated by applying the crack band theory (Bazant and Oh, 1983) and taking into account the plastic strain of concrete under tension. A simple procedure for calculating the stressstrain curve of plain concrete under tension was developed and implemented into the nonlinear finite element formulation. The proposed model gives relatively good agreement with the experimental results.